p53 Specifically Binds Triplex DNA In Vitro and in Cells - Brázdová, Marie; Tichý, Vlastimil; Helma, Robert; Bažantová, Pavla; Polášková, Alena; Krejčí, Aneta; Petr, Marek; Navrátilová, Lucie; Tichá, Olga; Nejedlý, Karel; Bennink, Martin L; Subramaniam, Vinod; et al. (PloS one, 2016)
Triplex DNA is implicated in a wide range of biological activities, including regulation of gene expression and genomic instability leading to cancer. The tumor suppressor p53 is a central regulator of cell fate in response to different type of insults. Sequence and structure specific modes of DNA recognition are core attributes of the p53 protein. The focus of this work is the structure-specific binding of p53 to DNA containing triplex-forming sequences in vitro and in cells and the effect on p53-driven transcription. This is the first DNA binding study of full-length p53 and its deletion variants to both intermolecular and intramolecular T.A.T triplexes. We demonstrate that the interaction of p53 with intermolecular T.A.T triplex is comparable to the recognition of CTG-hairpin non-B DNA structure. Using deletion mutants we determined the C-terminal DNA binding domain of p53 to be crucial for triplex recognition. Furthermore, strong p53 recognition of intramolecular T.A.T triplexes (H-DNA), stabilized by negative superhelicity in plasmid DNA, was detected by competition and immunoprecipitation experiments, and visualized by AFM. Moreover, chromatin immunoprecipitation revealed p53 binding T.A.T forming sequence in vivo. Enhanced reporter transactivation by p53 on insertion of triplex forming sequence into plasmid with p53 consensus sequence was observed by luciferase reporter assays. In-silico scan of human regulatory regions for the simultaneous presence of both consensus sequence and T.A.T motifs identified a set of candidate p53 target genes and p53-dependent activation of several of them (ABCG5, ENOX1, INSR, MCC, NFAT5) was confirmed by RT-qPCR. Our results show that T.A.T triplex comprises a new class of p53 binding sites targeted by p53 in a DNA structure-dependent mode in vitro and in cells. The contribution of p53 DNA structure-dependent binding to the regulation of transcription is discussed.
Keywords: DNA vazebné proteiny; Tumor Suppressor Protein p53; sekvenční delece; vazebná místa; DNA; lidé; regulační oblasti nukleových kyselin; Nucleic Acid Conformation; konformace nukleové kyseliny; nukleotidové motivy; plazmidy; Regulatory Sequences, Nucleic Acid; nádorový supresorový protein p53; DNA-Binding Proteins; aktivace transkripce; Nucleotide Motifs; Plasmids; promotorové oblasti (genetika); Promoter Regions, Genetic; Sequence Deletion; Transcriptional Activation; Binding Sites; Humans